2020
DOI: 10.3390/brainsci10100750
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation and Suicidal Attempts in Referred Adolescents with High Functioning Autism Spectrum Disorder and Comorbid Bipolar Disorder: A Pilot Study

Abstract: Suicidal ideation and attempts in adolescents are closely associated to bipolar disorders (BD). Growing evidence also suggests that high functioning autism spectrum disorders (HF-ASD) are at increased risk for suicidal ideation and behaviors. Although BD and HF-ASD are frequently comorbid, no studies explored suicidality in these individuals. This exploratory study addressed this issue in a clinical group of inpatient adolescents referred to a psychiatric emergency unit. Seventeen adolescents with BD and HF-AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 73 publications
1
18
0
2
Order By: Relevance
“…These findings may lead to hypothesize a greater load of autism spectrum features and, possibly, of neurodevelopmental alteration severity, in BD than in BPD [ 55 ]. However, in line with previous studies in this field, our results highlighted higher ruminative thinking and suicidality tendencies in both the clinical groups than in the CTL group, without significant differences between BD and BPD subjects [ 16 , 20 , 36 , 37 , 38 ]. Suicidal thoughts seem to be very common among individuals with ASD [ 56 , 57 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings may lead to hypothesize a greater load of autism spectrum features and, possibly, of neurodevelopmental alteration severity, in BD than in BPD [ 55 ]. However, in line with previous studies in this field, our results highlighted higher ruminative thinking and suicidality tendencies in both the clinical groups than in the CTL group, without significant differences between BD and BPD subjects [ 16 , 20 , 36 , 37 , 38 ]. Suicidal thoughts seem to be very common among individuals with ASD [ 56 , 57 ].…”
Section: Discussionsupporting
confidence: 92%
“…Noticeably, a recent study highlighted that also subjects with autistic traits show an increased suicidality risk, without significant differences with respect to the risk reported among individuals with ASD [ 25 ]. Previous studies also reported higher levels of suicidal ideation among both BD and BPD subjects with comorbid autistic traits [ 16 , 20 , 36 , 41 ].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…De hecho, los estudios previos señalan como limitante este aspecto no considerado. No obstante, algunas investigaciones mencionan que la red del apoyo social (familiares, amigos y comunidad) y la misma calidad de este apoyo, es un factor de protección en la presencia de pensamientos suicidas (Hedley et al, 2018), como también el apoyo tangible vinculado a la disponibilidad y ayuda sustancial (Hedley et al, 2017); mientras que otro estudio señala que algunas dimensiones de la resiliencia, como las competencias personales (capacidad personal, perseverancia y motivación), los estilos estructurados (capacidad de planificación y organización para los objetivos personales) y los recursos sociales (percepción de la red social de apoyo) son factores protectores en relación al desprecio por la vida y atracción por la muerte (Masi et al, 2020). Aquellos factores de protección son importantes para la adaptación del contexto, puesto que es crucial que las personas con TEA dispongan de recursos suficientes para afrontar los síntomas característicos y los problemas sociales, además de que reducen los comportamientos suicidas y fomentan la adherencia al tratamiento.…”
Section: Factores De Riesgo Y Protecciónunclassified